Implementation of Accounting Information Systems at Kitchen Veggie SMEs with Zahir Accounting Applications: Analysis of Effectiveness and Impact on Financial Management - Rachmani, Diah Ayu; Rahayu, Sri; Arum, Enggar Diah Puspa; Wiralestari, Wiralestari (Formosa Journal of Multidisciplinary Research, 2025)
This research aims to determine the effectiveness and impact of implementing the Accounting Information System (AIS) using the Zahir Accounting application on the UKM Kitchen Veggie, which operates in the culinary sector. The approach used in this research is qualitative with in-depth interview methods, field observations and document analysis. The research results show that the implementation of Zahir Accounting increases the efficiency of financial management, especially in recording transactions, managing cash flow, and preparing financial reports. In addition, this application simplifies raw material stock management and tax compliance by providing reports that are faster, more accurate and in accordance with applicable accounting standards. While there are challenges in user training and data integration, the positive impacts are far greater, such as increased transparency, reduced errors, and time savings. This research suggests that SMEs continue to maximize the use of this application to support organized and sustainable business growth.